Isolation of Actinobacteria from Date Palm Rhizosphere with Enzymatic, Antimicrobial, Antioxidant, and Protein Denaturation Inhibitory Activities - Maria Smati; Amina Bramki; Fatima Zohra Makhlouf; Rihab Djebaili; Beatrice Farda; Fatima Zohra Abdelhadi; Nahla Abdelli; Mahmoud Kitouni; Marika Pellegrini (Biomolecules)
Arid ecosystems constitute a promising source of actinobacteria producing new bioactive molecules. This study aimed to explore different biological activities of actinomycetes isolated from the rhizosphere of Phoenix dactylifera L. in the Ghardaia region, Algeria. A total of 18 actinobacteria were isolated and studied for their enzymatic and antimicrobial activities. All isolates shared cellulase and catalase activity; most of them produced amylase (94%), esterase (84%), lecithinase and lipoproteins (78%), caseinase (94%), and gelatinase (72%). The isolates could coagulate (56%) or peptonize (28%) skim milk. Overall, 72% of the isolates exhibited significant antibacterial activity against at least one test bacteria, while 56% demonstrated antifungal activity against at least one test fungi. Based on enzyme production and antimicrobial activity, isolate SGI16 was selected for secondary metabolite extraction by ethyl acetate. The crude extract of SGI16 was analyzed using DPPH and BSA denaturation inhibition tests, revealing significant antioxidant power (IC50 = 7.24 ± 0.21 μg mL−1) and protein denaturation inhibitory capacity (IC50 = 492.41 ± 0.47 μg mL−1). Molecular identification based on 16S rDNA analysis showed that SGI16 belonged to the genus Streptomyces. The findings highlight that date palms’ rhizosphere actinobacteria are a valuable source of biomolecules of biotechnological interest.